Coordinated collective migration and asymmetric cell division in confluent human keratinocytes without wounding - Lång, Emma (Nat Commun, 2018)
Epithelial sheet spreading is a fundamental cellular process that must be coordinated with cell division and differentiation to restore tissue integrity. Here we use consecutive serum deprivation and re-stimulation to reconstruct biphasic collective migration and proliferation in cultured sheets of human keratinocytes. In this system, a burst of long-range coordinated locomotion is rapidly generated throughout the cell sheet in the absence of wound edges. Migrating cohorts reach correlation lengths of several millimeters and display dependencies on epidermal growth factor receptor-mediated signaling, self-propelled polarized migration, and a G(1)/G(0) cell cycle environment. The migration phase is temporally and spatially aligned with polarized cell divisions characterized by pre-mitotic nuclear migration to the cell front and asymmetric partitioning of nuclear promyelocytic leukemia bodies and lysosomes to opposite daughter cells. This study investigates underlying mechanisms contributing to the stark contrast between cells in a static quiescent state compared to the long-range coordinated collective migration seen in contact with blood serum.